AN ANALYSIS OF FIGURATIVE LANGUAGE FOUND IN SONG LYRICS OF THE ALBUM OF GG BB XX BY LANY - Danisa Salsabila; Ratini Setyowati (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2024)
Sometimes people will face problems understanding the songâ€™s meaning. One of the reasons is caused by the use of Figurative Language. Therefore, this study analyzes about figurative language found in LANY's song lyrics in the "gg bb xx" album. The objectives of this study are to analyze the types and meaning of figurative language, and to explain the function of figurative language, also to find out the most dominant of figurative language. The objective of this research is to analysis of figurative language in the song lyrics of LANYâ€™s Album â€œgg bb xxâ€. In recent decades, linguistic scholars have focused their attention on the study of figurative language in song lyrics, however the song lyrics in LANYâ€™s songs havenâ€™t been explored using the figurative language theory. The problem of this research are to analyze the types and the most dominant figurative language found in song lyrics of the album â€œgg bb xxâ€ by LANY. The research used a descriptive qualitative method. The research data consisted of 12 song lyrics from LANY the album â€œgg bb xxâ€. This research used Perrine (2018) theories to analysis types of figurative language in â€œgg bb xxâ€ album. The results revealed that 36 types of figurative language were detected in the song lyrics, namely: 5 personification, 3 simile, 6 hyperbole, 7 metaphor, 2 irony, 2 understatement, 3 paradox, 1 apostrophe, 1 metonymy, 1 allegory, and 5 symbol. The data clearly show that metaphor was the most dominant type of figurative language in this result.